Pemahaman Makna Keterampilan Berpikir Tingkat Menengah (MOTS) dalam Pembelajaran Pendidikaan Agama Kristen - Marthen Mau; Sabudin Sabudin; Eliantri Putralin; Saenom Saenom; Henni Somantik; Markus Amid; Felipus Nubatonis (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
Middle order thinking skills (MOTS) questions are very important in Christian religious education learning. Evaluation of Christian religious education learning needs to be carried out by educators (teachers) based on each learning material so that students' academic achievement can be achieved well. In general, educators (teachers) do not fully understand the concept of middle order thinking skills (MOTS), as well as low order skills (LOTS) and high order skills (HOTS), so that some students find it difficult to answer questions given by educators (teachers) during learning evaluations. The type of research used is qualitative research with a literature review/literature study approach. The purpose of the study is to explain the understanding of the meaning of MOTS in Christian religious education learning on materials that are in accordance with learning objectives, so that students' academic achievement can be achieved well through learning evaluations. The results of the study are students are able to answer questions well from the middle order thinking skills (MOTS) type of questions when educators (teachers) create learning evaluation questions based on learning materials. Conclusion; To create evaluation questions for Christian religious education learning that students can answer and achieve academic success, ideally, questions should be based on the learning material they have learned.